Smart Cultural Heritage : Strategi Wujudkan Kelestarian Budaya di Era Smart City Terintegrasi Augemented Reality Melalui Platform Mojangki.id - Siska Nurnaningati; Tri Ayu Mukaromatul; Elvina Eka Saputri (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Smart City is the first step with the concept of a region that combines information and communication technology packaged with regional authenticity. Smart City aims to help provide better public services. With several government regulations that have developed related to smart cities, it is hoped that technological developments can improve the quality of life of the people so as to encourage sustainability. The forerunner in moving towards a smart city is seen from the potential of an area that can be developed. Smart Cultural Heritage is a regional concept that combines technology with cultural heritage to promote, enhance, and preserve culture by involving technologies such as Augmented Reality (AR), Virtual Reality (VR) and others. Tulusbesar Village is a village located in Tumpang District, Malang Regency which is rich in culture, but on the other hand the community does not have the ability to utilize technology in its development. The PPK Ormawa BEM FEB UM team initiated Mojangki.id innovations made with the needs of the community in the field of arts and culture to increase the Cultural Capital of Tulusbesar Village so that Mojangki.id innovations have a positive impact on increasing profits and managing tourism assets of Tulusbesar Cultural Village.